A case of rheumatoid arthritis with methotrexate related lymphoproliferative diseases of the knee. Issue 3 (4th May 2018) - Abe, Asami; Wakaki, Kunihiko; Ishikawa, Hajime; Ito, Satoshi; Murasawa, Akira
Abstract: Methotrexate (MTX) is the first choice disease-modifying antirheumatic drug (DMARD) for rheumatoid arthritis (RA) and is referred to as an "anchor drug"; its use has been steadily increasing annually. However, MTX-related lymphoproliferative diseases (MTX-LPDs) have emerged as important complications in the patients with RA. There have been no reports of intra-articular MTX-LPDs of the patients with RA. Atypical cells were found in the patient's joint fluid by cytological examinations, and MTX-LPDs were suspected. The patient discontinued MTX and open synovectomy was performed. The histological findings and immunohistochemical staining of the specimens confirmed the diagnosis of diffuse large B-cell lymphoma (DLBCL) of MTX-LPDs. After the operation of the patient's left knee joint, pains and swollen joint disappeared with no relapse. The cytological examinations of the synovial fluid followed by knee operation were effective for early diagnosis of MTX-LPD. MTX discontinuation with no chemotherapy followed up with a knee operation improved the recovery of the MTX-LPD.